2013
DOI: 10.1017/s1368980013002474
|View full text |Cite
|
Sign up to set email alerts
|

Family structure and childhood obesity: results of the IDEFICS Project

Abstract: Objective: To analyse the association between family structure and adiposity in children. Design: Cross-sectional and longitudinal analysis of the IDEFICS (Identification and prevention of dietary-and lifestyle-induced health effects in children and infants) study cohort. Setting: Primary schools and kindergartens. Subjects: Children (n 12 350; aged 7?9 (SD 1?8) years) for the cross-sectional analysis and children (n 5236; at baseline: normal weight, aged 5?9 (SD 1?8) years) for the longitudinal study underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 29 publications
1
66
1
1
Order By: Relevance
“…Over the 2-year follow-up, the risk of overweight/obesity was significantly lower with the higher number of siblings living in the household [23]. A study conducted in Santiago included 652 children, found higher number of siblings was protective (6-68% less risk for 2 siblings compared with no sibling and 10-73% less for ≥ 3 siblings) [24]. Several studies in Japan have investigated the relationship between the number of siblings and childhood overweight.…”
Section: Monthly Incomementioning
confidence: 99%
“…Over the 2-year follow-up, the risk of overweight/obesity was significantly lower with the higher number of siblings living in the household [23]. A study conducted in Santiago included 652 children, found higher number of siblings was protective (6-68% less risk for 2 siblings compared with no sibling and 10-73% less for ≥ 3 siblings) [24]. Several studies in Japan have investigated the relationship between the number of siblings and childhood overweight.…”
Section: Monthly Incomementioning
confidence: 99%
“…Families can exert a strong influence on children's diets, physical activities, and sedentary behaviours . Much research has focused on at‐risk parental characteristics and revealed that low parental socioeconomic status (SES) and lone‐parenthood are associated with increased risk of overweight and obesity in children . In addition to parental influence, an increasing number of studies have focused on grandparental influence as three‐generation family households become more prevalent or remain common worldwide in response to the rise of divorce, poverty, and female labour force participation …”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that children in single parent family, reconstituted families, or family without patents were more likely to have unhealthy eating habits such as irregular breakfast consumption, eating less vegetable, and drinking alcohol compared to children living with both parents [7,8,9,10]. Also, there are several studies which suggest a positive association between child health including obesity, asthma and family structure in single-mother families and custodial grandparent families [11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…While several studies have investigated an association of family structure with children's eating habit, health and well-being [7,8,9,10,11,12,13,14,15,16,17], studies that have examined the association with children's food intake are scarce. Diversity and adequacy of foods which compose meals should also be taken into account in assessment of nutritional status [18].…”
Section: Introductionmentioning
confidence: 99%